Analisis kesalahan sintaksis dalam buku كلامنا SMP Sabilillah Sampang - Mamnunah Mamnunah; Syihabuddin Syihabuddin (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2021)
At present we have often found that Arabic in Indonesia began to be studied from the level of Madrasah Ibtidaiyah or equivalent to the Higher Education. Sabilillah Sampang Middle School is one of the schools that opens opportunities for students who want to learn and want to explore Arabic. In teaching Arabic for its students, this school has produced a book called كلامنا that was created by teaching teachers who teach Arabic in this school. the forms of error in the book كلامنا include Khabar which consists of isim ghayru munsharif, Na'at man’ut there is the sentence الزرافة تملك العنق طويل which composition is included in the man's na'at. Al-Things contained in the word الحلزون يمشي بطيئ جدا, Maf'ul which contained the sentence أخذت أختي أبوا الشوكة على الشجرة which died أبوا is a death that should have been taken by the أخذت أختي أبوا الشوكة على الشجرة where the deceased أبوا is a death which should be translated by the Nashab because it became maf'ul bhafa نعاسٌ جدا, this analysis is carried out so that the errors in this book are considered, because if these errors are not corrected it will be rooted in students' knowledge.